Vacuum energy sequestering and graviton loops - Kaloper, Nemanja; Padilla, Antonio (American Physical Society, 2017)
We recently formulated a local mechanism of vacuum energy sequester. This mechanism automatically removes all matter loop contributions to vacuum energy from the stress energy tensor which sources the curvature. Here we adapt the local vacuum energy sequestering mechanism to also cancel all the vacuum energy loops involving virtual gravitons, in addition to the vacuum energy generated by matter fields alone.